Productive performance, chemical characterization and energy contribution of Megathyrsus maximus vc. Tanzania - Pincay Ronquillo, W.; Gavilánez Buñay, Tatiana; Verdecía Acosta, D.M.; Chacón Marcheco, E.; Ramírez de la Ribera, J.L.; Herrera, R.S. (Cuban Journal of Agricultural Science, 2024)
With the objective of evaluating the productive performance, chemical characterization, digestibility and energy contribution of Megathyrsus maximus vc. Tanzania at different regrowth ages, in both periods of the year, and under climatic condition of Granma province, a random block design with four replications was used. It was sampled in 25 m2plots, to which uniformity cut at 10 cm from the soil was applied, without irrigation and fertilization. It was determined the yield of total dry matter, leaves and stems; the length and width of leaves; leaf-stem proportion; the chemical composition (CP, NDF, ADF, ADL, CC, Si, P, Ca, ash and OM); energy contribution and digestibility. Analysis of variance of each studied variable was applied. The yields were higher at 75 days with 4.02 and 2.56 tDM/ha/cut in the rainy and dry season, respectively, the crude protein decreased with the age in both seasons and showed significant differences among all ages. The best values were showed at 30 regrowth days (9.44 and 10.11 % in the rainy and dry seasons, respectively), the fiber increase with the age with their higher values at 75 days with 68.04 and 67.45 % in the rainy and dry seasons, respectively, aspects that determine the quality with decrease of digestibility and energy contribution. The plant yield was affected by the seasons of the year, being higher in the rainy season. It is concluded that the evaluated cultivar has adequate morphological and productive performance under low rainfalls conditions, so is a viable option for animal feeding.